Registration of the S2MET Barley Mapping Population for Multi‐Environment Genomewide Selection. Issue 2 (14th March 2019) - Neyhart, Jeffrey L.; Sweeney, Daniel; Sorrells, Mark; Kapp, Christian; Kephart, Kenneth D.; Sherman, Jamie; Stockinger, Eric J.; Fisk, Scott; Hayes, Patrick; Daba, Sintayehu; Mohammadi, Mohsen; Hughes, Nia; et al.
Abstract : Market changes in the malting and brewing industries have increased the demand for locally produced barley ( Hordeum vulgare L.) in many regions across North America. Breeding for productive barley cultivars in diverse growing environments is complicated by genotype × environment interactions (GEIs), which can make selection for broad adaptation difficult but may be exploited to select optimal cultivars for each environment. Genomewide selection has recently become a useful tool to make efficient selections on individuals using genomewide marker data. To support the use of genomewide selection to breed locally adapted barley cultivars, the University of Minnesota barley breeding program is publicly releasing a panel of two‐row barley lines, and accompanying data, called the S2MET (Spring Two‐Row Multi‐Environment Trial) (Reg. No. MP‐2, NSL 526938 MAP). The S2MET includes 233 breeding lines grouped into a 183‐line training population and a 50‐line validation population. The entire panel was genotyped using genotyping‐by‐sequencing and phenotyped for 14 important traits in 44 location‐year environments between 2015 and 2017. All data are freely available at the Triticeae Toolbox (https://triticeaetoolbox.org/barley/ ), and we describe several on‐tap projects and breeding advances that are exploiting this resource. We believe this panel and dataset will be useful for answering important breeding questions related to genomewide selection and GEIs and developing locally superior barley cultivars.